Comparative study of mitotic chromosomes in two blowflies, Lucilia sericata and L. cluvia (Diptera, Calliphoridae), by C- and G-like banding patterns and rRNA loci, and implications for karyotype evolution - Mónica G. Chirino; Luis F. Rossi; María J. Bressa; Juan P. Luaces; María Susana Merani (Comparative Cytogenetics, 2015)
The karyotypes of Lucilia cluvia (Walker, 1849) and L. sericata (Meigen, 1826) from Argentina were characterized using conventional staining and the C- and G-like banding techniques. Besides, nucleolus organizer regions (NORs) were detected by fluorescent in situ hybridization (FISH) and silver staining technique. The chromosome complement of these species comprises five pairs of autosomes and a pair of sex chromosomes (XX/XY, female/male). The autosomes of both species have the same size and morphology, as well as C- and G-like banding patterns. The X and Y chromosomes of L. cluvia are subtelocentric and easily identified due to their very small size. In L. sericata, the X chromosome is metacentric and the largest of the complement, showing a secondary constriction in its short arm, whereas the Y is submetacentric and smaller than the X. The C-banding patterns reflect differences in chromatin structure and composition between the subtelocentric X and Y chromosomes of L. cluvia and the biarmed sex chromosomes of L. sericata. These differences in the sex chromosomes may be due to distinct amounts of constitutive heterochromatin. In L. cluvia, the NORs are placed at one end of the long-X and of the long-Y chromosome arms, whereas one of the NORs is disposed in the secondary constriction of the short-X chromosome arm and the other on the long-Y chromosome arm in L. sericata. Although the G-like banding technique does not yield G-bands like those in mammalian chromosomes, it shows a high degree chromosomal homology in both species because each pair of autosomes was correctly paired. This chromosome similarity suggests the absence of autosomal rearrangements during karyotype evolution in the two species studied.